2006
DOI: 10.1111/j.1467-6486.2006.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the HRM–Performance Link: Value‐Creating and Cost‐Increasing Effects of Small Business HRM*

Abstract:  The majority of empirical studies on the HRM-performance link report a positive story. The costs associated with the productivity rise due to high performance work practices (HPWP) have been largely neglected. The purpose of this study is to develop a conceptual framework that maps both the value-enhancing and cost-raising impact of HPWP. In addition, we want to pronounce upon their overall effect on financial performance. To test our model, we rely on a sample of small businesses. Understanding both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
1
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(207 citation statements)
references
References 83 publications
10
186
1
10
Order By: Relevance
“…In our study, fewer ability and motivation practices were reported by our sample of employees working in the smaller firms (Hypothesis 1). The costs involved in implementing formal training (A), career paths and high salaries (M) can be substantial and particularly difficult to shoulder by smaller firms (Sels et al 2006). In addition, the greater organisational complexity of larger firms and the increased difficulty in these firms to maintain direct control through an informal approach will lead to the implementation of more formalised ability and motivation practices (Mayson and Barrett 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, fewer ability and motivation practices were reported by our sample of employees working in the smaller firms (Hypothesis 1). The costs involved in implementing formal training (A), career paths and high salaries (M) can be substantial and particularly difficult to shoulder by smaller firms (Sels et al 2006). In addition, the greater organisational complexity of larger firms and the increased difficulty in these firms to maintain direct control through an informal approach will lead to the implementation of more formalised ability and motivation practices (Mayson and Barrett 2006).…”
Section: Discussionmentioning
confidence: 99%
“…First, not as many organisations have adopted HPWP systems as might be expected given the claimed advantages (Kauhanen 2009). This seems to be especially the case with small organisations (Sels et al 2006). Second, the practices said to constitute a HPWPs vary from one research project to another, leading to the observation that as few as four practices seem to be consistently part of the HPWP 'system' measured by researchers Boxall and Macky 2009): (1) training and development, (2) contingent pay and reward schemes, (3) performance management (including appraisal) and (4) careful recruitment and selection.…”
Section: Hpwps and The Amo Modelmentioning
confidence: 99%
See 3 more Smart Citations